Antioxidant and anti-staphylococcal activity of polyphenolic-rich extracts from Ataulfo mango seed. (August 2021) - Torres-León, Cristian; de Azevedo Ramos, Bárbara; dos Santos Correia, Maria T.; Carneiro-da-Cunha, Maria G.; Ramirez-Guzman, Nathiely; Alves, Luiz C.; Brayner, Fabio A.; Ascacio-Valdes, Juan; Álvarez-Pérez, Olga B.; Aguilar, Cristóbal N.
Abstract: In recent years, the search for new antioxidant and antimicrobial agents is one of the first subjects of scientific research. The polyphenolic compounds of food byproducts have attracted scientists across the world in the search for new natural substances. In this study, antioxidant (DPPH, ABTS, and TAA) and anti- Staphylococcus aureus (ATCC and clinical isolates strains) activity of mango seed extracts was investigated. The extracts were obtained by Microwave-Assisted Extraction (MAE), Fermentation-Assisted Extraction (FAE), and Solvent-Assisted Extraction (SAE). Chemical profile as well as influence of applied extraction technique were also investigated. The extracts showed potent antioxidant activity with EC50 values (MAE: 27.1 ± 0.15 μg/mL, SAE:14.3 ± 0.37 μg/mL and FAE:12.5 ± 0.41 μg/mL) higher than Trolox (for DPPH). Higher antibacterial activity was observed (MIC: 7.31–750 μg/mL and CMB: 156.3–1500 μg/mL) compared to synthetic antibiotics. Cell wall damage and cell lysis were clearly visualized under Scanning Electron Microscopy (SEM). HPLC–MS allowed the detection of 6 (SAE), 8 (MAE), and 11 (FAE) polyphenolic compounds. These findings suggest that Ataulfo mango seed extracts may be utilized in the developed natural antioxidant and antibacterial agents. Highlights: The mango seed is a source of powerful natural antioxidants and antimicrobials. Mechanism of action of mango seed against S. aureus has been elucidated. HPLC–MS is applied for identification of polyphenolic compounds. The biological activity of the majority compound PGG was evaluated. Legends of figures.